Improving surgical inpatient ward lists in a large acute hospital: a simple yet effective process to save the time of junior house officers. Issue 1 (18th June 2014) - Kenny, Ross; Johnston, Carolyn; Qureshi, Imran
Abstract: In order for the smooth running of a surgical firm, an effective ward list must be created, updated, and edited each day, often by junior medical personnel. Ward lists are used by various healthcare professionals including consultants, specialist nurses, and pharmacists. Over time ward inpatient lists can become increasingly difficult to use and lacking in vital information. Baseline measurement revealed the extent of the problem with junior house officers spending on average 95 minutes per day maintaining the ward list. After a period of research and learning, a bespoke inpatient list was created containing all of the vital information required. Criteria to fulfil included being straightforward to manipulate, easy to input new patients and aesthetically pleasing. After a trial period with modifications, an improved inpatient ward list was successfully implemented. Post-intervention data collection revealed a reduction of 42 minutes per day on average spent maintaining the list, with a 100% increase in satisfaction, and reduction in problems encountered from daily to weekly. Following this success, the general surgery weekend handover list was improved using the same prototype. This led to a saving of 8 minutes per day on average and increased doctor satisfaction. The process of creating an effective, easy to use, and useful inpatient ward list can lead to large amount of time saved each day for the staff responsible for its management. This time can then be reinvested on clinical duties, or education, to further improve the healthcare service we provide.